An epigenetic analysis of planarian stem cells - Dattani, A (2018)
Planarian flatworms possess somatic pluripotent stem cells, called neoblasts (NBs), which are able to differentiate into all cell types that constitute the adult body plan. Consequently, planarians possess remarkable regenerative capacities, and have become an invertebrate model system to study stem cell responses during regeneration. Transcriptomic studies have revealed the genes needed to both maintain NB pluripotency and ensure correct lineage specification during differentiation. However, these studies have not elucidated how this regulation of expression is controlled at the epigenetic level, and in particular by diverse histone modifications. In this thesis, we present a case for elevating planarians as a model system for studying the epigenetic regulation of stem cell pluripotency and differentiation. Firstly, we describe an expression-based annotation of the asexual Schmidtea mediterranea genome. For each annotated locus, we allocate proportional values for a gene’s expression in either S/G2/M NBs (X1), G1 NBs + post-mitotic progeny (X2), or differentiated cells (Xins) – the three broadly-defined cellular compartments that can be isolated from planarians using Fluorescence Activated Cell Sorting (FACS). The production of a well-annotated genome incorporating transcriptomic information serves as the basis for correlating the presence of particular histone modifications with underlying gene expression. We have developed an optimized ChIP-seq protocol for planarian NBs and show that the active histone marks H3K4me3 and H3K36me3 and suppressive H3K4me1 and H3K27me3 marks correlate with the transcriptional output of genes. We also show that genes with little transcriptional activity in NBs, but which switch on in post-mitotic progeny during differentiation are bivalent, being marked by both H3K4me3 and H3K27me3 at the promoter-proximal region. Bivalent histone modifications in mammalian embryonic and germline stem cells enable transcriptional poising of genes, and consistent with this we find that bivalent genes in planarian NBs are marked by paused RNA Pol II at the promoter-proximal region. In addition to histone modifications, enhancers and their associated transcription factors can also directly influence gene expression. Consequently, we elucidate the potential TF repertoire of planarians, and identify those enriched in NBs. We also present preliminary evidence to suggest that ATAC-seq on planarian cells can identify both transcriptionally permissive gene promoters, at least in differentiated cells, as well as putative enhancers that correlate with expression of neighbouring genes. In the future, we hope to be able to build gene regulatory networks by identifying TF-binding sites in open chromatin regions and elucidating enhancer targets in a range of planarian cell types.